Teachers’ Strategies in Teaching Reading Comprehension to the Second-Grade Students of Senior High School - Anggi Oktavia Nur HS; Kisman Salija; Munir Munir (Journal of Excellence in English Language Education, 2023)
The purpose of this study is to find out teacher strategies in teaching reading comprehension at SMAN  2 Jeneponto. Based on the research problem, it is evident that the purpose of this study is to describe the tactics employed by English teachers in teaching English to second-grade students at Senior High School 2 Jeneponto. This study is descriptive qualitative. Observation interviews and documentation were used to compile the data. The tactics for improving students' reading skills were based on Jeremy Harmer's premise of teaching reading: "Reading is not a passive ability; students must be involved with what they are reading." And the students' reactions are positive, with the majority of them finding the teaching reading skills to be enjoyable and interesting. This research shows that teachers employ many teaching strategies in teaching reading comprehension, including scaffolding and the QAR strategy. According to this study, those tactics are beneficial in teaching reading comprehension since they can aid students in understanding the material. Students who struggle with reading will find it easier to grasp reading comprehension. The teacher can more readily give the material to the students when they utilize this technique. Because the students are more engaged, those tactics can benefit the teacher. Students can also discuss their ideas with their friends.